Subacromial Balloon Arthroplasty: Development of a Rehabilitation Protocol through Literature Review - Engenheiro, Gonçalo Gomes; Serviço MFR - Centro Hospitalar de Entre o Douro e Vouga (CHEDV) (2022)
Introduction: Subacromial balloon arthroplasty is a promising new arthroscopic solution for massive to irreparable rotator cuff tears, consisting of insertion of a biodegradable device into the subacromial space. Despite the growing interest in this procedure since it was introduced in 2012, details concerning postoperative rehabilitation are yet very scarce.Our objective was to develop a rehabilitation protocol following subacromial balloon insertion without rotator cuff tear repair based on literature review.Methods: To develop the protocol, we reviewed the available literature in Scopus, Web of Science and PubMed until 2020, and collected experts’ opinion in PRM and Orthopedics departments of our institution.Results: We found 9 studies including information on postoperative rehabilitation. Duration of rehabilitation was 12 weeks. Main goals were: regaining range of motion, strength, and scapulotoracic balance. Shoulder immobilization was required for 1 to 4 weeks. Range of motion started in the first days, with variable progression. Strengthening began by the third/fourth weeks. Overhead activity was usually allowed after 6 weeks.Conclusion: According to these findings, we elaborated a 12-week rehabilitation program divided into 4-week blocks, focused on flexibility and early strengthening of scapular depressors and stabilizers to promote the lowering of the humeral head achieved by the balloon implantation. The ultimate goal is to recover independence in activities of daily living. The protocol presented in this article addresses the lack of proper details on the subacromial balloon arthroplasty postoperative rehabilitation process. In the future, prospective studies are warranted to provide evidence of the effectiveness of this comprehensive program.